The Mantle of Teachers’ Mathematics Pedagogical Content Knowledge in Teaching and Learning of Grade 12 Mathematics - Pule, Gilbert Kereng; Bhagwonparsadh, Yudvir (Research in Social Sciences and Technology, 2025)
This exploratory qualitative case study inquired into teachers' Mathematics Pedagogical Content Knowledge and the teaching and learning of Grade 12 Mathematics at two selected secondary schools. Four Mathematics teachers shared their enactment of the teaching and learning of Grade 12 Mathematics when semi-structured interview questions were posed. Further, the teachers' pedagogical content knowledge impacts positively on the learning of Gr 12 learners in Mathematics in the context of a child-centred paradigm of teaching and learning. In addition, the research findings suggest that Mathematics teachers should be subject specialists, generate instructional content that will promote higher-order cognition in learners, can facilitate independent and group work to encourage learners' achievement levels striving towards high Grade 12 achievement still-general exit. Further, Mathematics teachers are expected to use a range of methodological practices relevant to the diverse learning capabilities and needs of all learners in the classroom, therefore enabling students to master content through learner-centred activities. Teachers have to facilitate learning by making abstract content concrete and interactive and get learners actively involved in collaborative group activities for Grade 12 Mathematics learners a success. The study also suggested that Grade 12 Mathematics teachers require professional development to learn learner-centred strategies in the teaching and learning of Mathematics.